Engagement of Occupational Safety and Health at Mahkamah’s Welding Worker Medan - Mahyuni, Eka; Kalsum,; Sinaga, Muhammad Makmur (Journal of Saintech Transfer, 2018)
Welding worker was not the easy task because it has a very high physical risk and the process requires special skills and equipment to prevent accident exposed. This devotional activity is carried out in the welding industry at Jl. Mahkamah with two partners, namely CV. M. Nauli and CV. Cahaya. The aim of training activity made the worker able to analyze the hazards in the workplace so that it will be more careful in their work. The result show that the training could develop the worker to be aware about safety and health work patterns. In order to support the work in accordance with occupational safety and health standards, workers are also given pocket books that contain safety and health working methods and also given the self-protection of welding like welding clothes, welding gloves, welding mask, welding glasses and masks. Based on the evaluation of activities, it show that the worker has develop and always using the self protector in their work evenly. It build the good collaboration between them and they are could arrage the rest time with ergonomics relaxation in 5-10 minutes. The workshop station looks better than before and the workshop doing good house keeping before and after their work.